Hidradenoma papilliferum of the external auditory canal. Case report - Laababsi, Rabii (Ann Med Surg (Lond), 2019)
INTRODUCTION: Hidradenoma papilliferum, also known as papillary hidradenoma, is a rare tumor of the sudoral glands, that occurs almost exclusively in women, on the vulvar and perineal region. Non-genital papillary hydradenoma is an even more rare occurrence, though some cases have been described in literature. This is a report of a 56 years old patient who presented with unilateral hearing loss secondary to a mass of the external auditory canal (EAC). A biopsy allowed us to make the diagnosis of a papillary hidradenoma of the EAC. The treatment was based on surgery; the tumor was removed while respecting the adjacent structures. Follow-up of the patient shows no actual recurrence. CONCLUSION: Ectopic Hidradenoma papilliferum located in the EAC is a rare occurrence, and should be considered as a possible diagnosis when investigating a mass of the EAC.